1992
DOI: 10.1159/000288575
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Medical Hospital Length of Stay by Depression in Stroke and Amputation Patients: A Pilot Study

Abstract: Past studies have found that medical patients with the diagnosis of depression (comorbidity) have longer hospital lengths of stay (LOS) than those without the diagnosis of depression. This suggested that scores on a depression scale would be positively correlated with LOS. On a rehabilitation ward, 14 stroke and 17 amputee patients were given the Geriatric Depression Scale (GDS) and lengths of stay were recorded. Correlations between GDS scores and LOS were + 0.575 for stroke and + 0.266 for amputee patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
7

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 12 publications
0
27
0
7
Order By: Relevance
“…2 PSD is common and associated with many negative consequences, including lengthened hospital stays, prolonged recovery time, increased mortality, and impaired functional outcomes. [3][4][5][6][7] Several studies have reported that stroke survivors with PSD or depressive symptoms may demonstrate worse functional outcomes, impairment, and recovery compared to those without depression. 3,4,8,9 Although many studies have linked PSD to worse functional outcomes, there is little known about the impact of PSD treatment and improvement on function after stroke.…”
mentioning
confidence: 99%
“…2 PSD is common and associated with many negative consequences, including lengthened hospital stays, prolonged recovery time, increased mortality, and impaired functional outcomes. [3][4][5][6][7] Several studies have reported that stroke survivors with PSD or depressive symptoms may demonstrate worse functional outcomes, impairment, and recovery compared to those without depression. 3,4,8,9 Although many studies have linked PSD to worse functional outcomes, there is little known about the impact of PSD treatment and improvement on function after stroke.…”
mentioning
confidence: 99%
“…Most studies have examined the impact of PSD on length of stay (LOS) in a rehabilitation setting, and their findings are equivocal. Some studies found an association between PSD and increased LOS (eg, Schubert et al 5 ), whereas other studies did not demonstrate such a relation (eg, Gillen et al 6 ). Recently, PSD among veterans has been found to be associated with more outpatient visits and an increase in the total length of rehospitalization in the 1-year 7 as well as the 3-year 8 period after initial stroke hospitalization.…”
mentioning
confidence: 99%
“…1 PSD is commonly unrecognized and untreated in clinical practice. 1,5 According to Schubert et al, 8 nonpsychiatric physicians fail to diagnose 50% to 80% of the actually existing depression. PSD has been related to physical handicap and the limitations in activities of daily living (ADL).…”
mentioning
confidence: 99%